2020
DOI: 10.3390/coatings10050472
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive Zinc Oxide Based Transparent Conductive Oxide Films Prepared Using RF Plasma Sputtering Under Reducing Atmosphere

Abstract: The spectral properties and colour functions of a radio frequency (RF)-based sputtering plasma source was monitored during consecutive sputter deposition of zinc doped indium oxide (IZO) thin films under argon and argon/hydrogen mix. The effect of target exposure to the hydrogen gas on charge density/mobility and spectral transmittance of the deposited films was investigated. We demonstrate that consecutive exposure to the hydrogen gas during the deposition process progressively affects the properties of thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…As can be seen from the results presented in Figure 4, the electrical properties of the deposited films significantly varied for ZnO, depending on the position for the substrate, while for IZO the variation was significantly less elaborated (comparing the associated edge and centre samples). In a previous study, we demonstrated the enhanced electrical properties of the IZO when deposited under the argon-hydrogen mix [29]. These results combined with the observations presented in Figure 3 suggest that one way to explain this is to assume that more hydrogen doping is occurring at the edge of the substrate compared to the centre, unless the thickness of the coating was causing this observation.…”
Section: Electrical Propertiessupporting
confidence: 55%
See 2 more Smart Citations
“…As can be seen from the results presented in Figure 4, the electrical properties of the deposited films significantly varied for ZnO, depending on the position for the substrate, while for IZO the variation was significantly less elaborated (comparing the associated edge and centre samples). In a previous study, we demonstrated the enhanced electrical properties of the IZO when deposited under the argon-hydrogen mix [29]. These results combined with the observations presented in Figure 3 suggest that one way to explain this is to assume that more hydrogen doping is occurring at the edge of the substrate compared to the centre, unless the thickness of the coating was causing this observation.…”
Section: Electrical Propertiessupporting
confidence: 55%
“…However, such reports only exist at the research state, and no commercial TCO based on pure ZnO doped with hydrogen is present in the market to the best of our knowledge. We recently reported on enhancing the electrical properties of IZO and ZnO systems by repeated exposure of the sputtering target to an argon/hydrogen mixture as the working gas [29]. We have now identified interesting complexities associated with reactive hydrogen/argon sputtering of un-doped ZnO targets, which we believe are associated with the reported magnetic properties of hydrogenated ZnO particles, and this report outlines our observations.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the recent years, through the work of Giuffredi et al [30,31] and Fominski et al [32], it was shown that plasma monitoring with ion probes can be a successful approach for in-situ analysis during formation of complex films. The real-time monitoring during the deposition process was extended to other techniques like magnetron sputtering [33,34], PECVD [35] or plasma spray [36,37].…”
Section: Introduction: a History Of Measurementsmentioning
confidence: 99%